Cost analysis of endodontic treatment in primary teeth: results from a randomized clinical trial - Suzana Cavalcanti Monteiro de Oliveira; Isabela Floriano; Tamara Kerber Tedesco; Thaís Gimenez; José Carlos Pettorossi Imparato; Ana Flávia Bissoto Calvo (Sociedade Brasileira de Pesquisa Odontológica, 2021)
Abstract: This study compared the cost of endodontic treatment in primary teeth involving a technique that does not require root canal instrumentation using antibiotic paste (CTZ) with that of the instrumented technique using iodoform paste (GP). This study is part of a randomized, controlled, parallel arm, noninferiority, 1:1 allocation, blinded (patient) multioperator study of 52 primary incisors of children aged 3 to 6 years with caries lesion and pulp involvement. Each technique was performed according to the creators' descriptions. The cost was assessed by analyzing the costs of capital, dental supplies, and professional labor according to the time taken to perform the procedure and the CHEERS guidelines were used to report the cost assessment. Endodontic treatment with CTZ had a 58.33% lower execution cost than GP (US$6.73 and US$16.15, respectively). The t-test showed significant differences between groups regarding treatment time and total cost (p < 0.0001). The CTZ technique seems to be more economically viable than GP for endodontic treatment of primary teeth, requiring a shorter treatment time and lower costs.